Prescriptive adherence to GINA guidelines and asthma control: An Italian cross sectional study in general practice. (January 2019) - ,; Angino, Anna; Baldacci, Sandra; Bresciani, Megon; Cerrai, Sonia; Di Pede, Francesco; Maio, Sara; Martini, Franca; Piegaia, Bona Barbara; Sarno, Giuseppe; Silvi, Patrizia; Viegi, Giovanni; et al.
Abstract: Background: Although general practitioners (GPs) are frequently the first healthcare professionals whom asthma patients refer to for their symptoms, few studies have explored the extent of adherence to guidelines for asthma management based on data provided directly by GPs. Aims of the present study were to assess drug prescriptions for asthma by GPs and to evaluate prescriptive adherence to GINA guidelines (GL) and its relationship with disease control in real life. Methods: 995 asthmatic patients (45% males, mean age 43.3 ± 17.7 yrs) were enrolled by 107 Italian GPs distributed throughout the country. Data on diagnosis, disease severity, prescribed anti-asthmatic drugs and control were collected through questionnaires filled out by GPs taking into consideration the 2009 GINA Guidelines. Data on drug use and chronic sinusitis, nasal polyposis, chronic bronchitis, emphysema were reported by patients through a self-administered questionnaire. Results: The large majority of patients were classified by GPs as having intermittent (48.4%) or mild persistent asthma (25.3%); 61% had co-morbid allergic rhinitis (AR). The prevalent therapeutic regimen used by patients was a combination of inhaled corticosteroids (ICS) plus long-acting β2 -agonists (LABA) (54.1%), even in the intermittent/mild persistent group. ICS as mono-therapy or in combination with other drugs but LABA, was the second most frequently adopted treatment (14.4%). In general, the GPs adherence to GL treatment indications was 28.8%, with a significant association with a good asthma control (OR 1.85, 95% CI 1.18–2.92). On the other hand, comorbidity (OR 0.52, 95% CI 0.32–0.84), moderate (0.44, 0.28–0.69) and severe (0.06, 0.02–0.20) persistent asthma showed significant negative effects on asthma control. Conclusions: Our results show that over-treatment of intermittent/mild persistent asthma is frequent in the GPs setting while therapeutic regimens are more appropriately applied for moderate/severe asthma. In general, we found low adherence to GINA GL treatment recommendations even if its relevance in asthma control was confirmed.